THE DETERMINANTS OF MATERNAL ANAEMIA VERSUS BIRTH WEIGHT OF NEWBORN, A COMPARATIVE STUDY AMONG NON-ANAEMIC AND ANAEMIC PREGNANT WOMEN IN A SELECTED TERTIARY CARE HOSPITAL, CHENGALPATTU DISTRICT, TAMILNADU. - Dr. G. Karpagavalli; Mrs Joselly Monickaraj; Mrs D Subitha Rani (The Bioscan, 2025)
Background: During pregnancy women with haemoglobin level less than 11 grams/decilitre in their red blood cells are said to have anaemia during pregnancy. Anaemia is one of the most common preventable medical condition that affect women during pregnancy. It is not only the greatest challenge but also an easily treatable problem faced by the developing countries, hence understanding the determinants of maternal anaemia is essential to boost the prophylactic and therapeutic management of anaemia during pregnancy. Methodology: Quantitative exploratory research approach was selected to compare the determinants of maternal anaemia and the foetal wellbeing among non-anaemic and anaemic pregnant women. The analytical cross-sectional design was used to study eighty two pregnant women (41 non-anaemic women and 41 anaemic women) who visited the labour ward at Chrompet government hospital, Tamil Nadu, India. A structured interview schedule was used to collect the determinants of maternal anaemia. Comparison of the determinants of maternal anaemia that affect the birth weight of the newborn among non-anaemic and anaemic pregnant women was done. Result: The comparison of the determinants in the study reveals that 43% of pregnant women at 21-25 years of age, pregnant women with obstetrical score at 44% of gravida 1 and gravida 2, 49% of para 2 and live birth 2 were anaemic. Majority of 81% of anaemic pregnant women belonged to nuclear family, 42% had a family income of 15,000 to 20,000 per month, 61% had SSLC level of education, 81% were unemployed, 91% were non-vegetarian, and 59% were at 39 weeks of gestation. Independent t-test of levels of haemoglobin among anaemic and non-anaemic pregnant women was 10.39±1.179 and 12.38±1.005 with statistical significant at p<0.001. There exist a statistically significant association amid the treatment given to the anaemic women and the birth weight at p<0.001. Conclusion: The statistically significant level of haemoglobin reveals that a homogenous group of pregnant anaemic and non-anaemic women with determinants such as 21-25 years of age, obstetrical score of G1P2L2 and G2P2L2, 39 weeks of gestation, nuclear family, non-vegetarian, family income, education, and unemployment were predominantly anaemic during pregnancy. The treatment given during pregnancy was statistically significantly associated with the birth weight of the anaemic pregnant women which indicates that special attention given to the women during pregnancy wound be effective to minimize the impact of anaemia on newborn.